Lightweight rPPU Eco-block Using Recycled Plastic (rP) and Polyurethane (PU) for Soft Subgrade Soil Stabilisation - Tuan Ismail, Tuan Noor Hasanan; Akma Qistina Khairulazuwar; Roslinda Ali; Salina Sani; Nur Faezah Yahya (Emerging Advances in Integrated Technology, 2024)
The stability of soil plays a crucial role in the safety and longevity of various civil engineering structures. However, problematic soil conditions, such as clay soil and peat soil, often pose challenges due to their high-water content, poor strength, low bearing capacity, and high compressibility. This research focuses on addressing these challenges by utilizing lightweight fill materials as an effective solution for backfilling applications. The study aims to investigate the characteristics and performance of a novel lightweight fill material using recycled plastic (rP) and polyurethane (PU) known as rPPU ecoblock. The eco-block is mainly fabricated using recycled plastic bottles, recycled plastic packaging, and polyurethane, offering a sustainable approach to waste management and construction materials. To achieve the research objectives, a series of experiments will be conducted. The strength and density of plastic bottles filled with recycled plastic packaging will be analyzed, providing insight into their mechanical properties. Furthermore, the water absorption and buoyancy of the lightweight rPPU eco-block are evaluated, considering its suitability for various construction scenarios. The research findings contribute to the understanding of the physical and mechanical characteristics of the rPPU eco-block, providing valuable information for its potential application as a backfill material. The compressive strength, water absorption, and buoyancy test conducted per ASTM standards provide quantitative data on the eco-block’s performance. The use of lightweight fill materials, particularly the rPPU eco-block, offers benefits such as reduced embankment self-weight, improved stability, and minimized environmental impact. Moreover, the recycling of plastic waste contributes to the circular economy and aligns with sustainable development goals (SDG): SDG9 and SDG11. The results of this research provide valuable insights for engineers, construction professionals, and stakeholders involved in geotechnical and civil engineering projects.